2009
DOI: 10.4049/jimmunol.0802526
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms Contribute to Impairment of Type 1 Interferon Production during Chronic Lymphocytic Choriomeningitis Virus Infection of Mice

Abstract: Type 1 IFNs, innate cytokines with important effector and immunomodulatory properties, are rapidly induced in the acute phase of many virus infections; however, this is generally a transient response that is not sustained during virus persistence. To gain insight into mechanisms that can contribute to down-regulation of type 1 IFN production during virus persistence, we analyzed type 1 IFN production during acute and chronic lymphocytic choriomeningitis virus (LCMV) infection. High-level type 1 IFN production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 64 publications
5
85
0
Order By: Relevance
“…Our previous studies have demonstrated that TLR2, TLR6, and CD14 are involved in LCMV-induced proinflammatory chemokines and cytokines (66). The mechanism by which LCMV induces type I IFN responses, however, has not been clearly defined (7,8,31,44). The role of the helicase family members RIG-I and MDA5 in virus-induced type I IFN responses has been recently established.…”
mentioning
confidence: 99%
“…Our previous studies have demonstrated that TLR2, TLR6, and CD14 are involved in LCMV-induced proinflammatory chemokines and cytokines (66). The mechanism by which LCMV induces type I IFN responses, however, has not been clearly defined (7,8,31,44). The role of the helicase family members RIG-I and MDA5 in virus-induced type I IFN responses has been recently established.…”
mentioning
confidence: 99%
“…Since immunological studies of virusinduced hepatitis in human are difficult to perform (reviewed in references 8 and 9), infections of mice with lymphocytic choriomeningitis virus (LCMV) have demonstrated to be a valid model system to examine intrahepatic antiviral immunity (reviewed in reference 10). Although mice persistently infected with LCMV exhibit altered innate responses to subsequent Toll-like receptor (TLR) stimulations and secondary infections (11,12), the overall and intrahepatic alterations of the innate immune system during early LCMV infections have been less studied.Monocytes survey the body for inflammatory foci and are …”
mentioning
confidence: 99%
“…Accordingly, HCV and LCMV have evolved mechanisms to block IFN induction in the infected cell (1,2). Nevertheless, HCV and LCMV infections strongly induce IFN and IFNstimulated gene (ISG) expression in vivo (3)(4)(5)(6)(7). Recently, we reported that Huh-7 cells infected with HCV or containing a subgenomic HCV replicon can trigger alpha/beta IFN (IFN-␣/␤) production in vitro by exosomal transfer of positive-strand HCV RNA to cocultured human peripheral blood-derived plasmacytoid dendritic cells (pDCs) in a Toll-like receptor 7 (TLR7)-dependent manner without infecting them (1,8,9).…”
mentioning
confidence: 99%
“…LCMV causes a longterm chronic infection in its natural host, the mouse. Human infections occur through mucosal exposure to aerosols or by direct contact of abraded skin with infectious material (3)(4)(5)(6)(7)11). LCMV infection of humans can result in severe disease that in some cases can be fatal (12).…”
mentioning
confidence: 99%